Business Feasibility Study Analysis of The Pianeta Ice Cream Dessert Business - Septihani Michella Wijaya; Patrice Febiyani Metty; Andi Wijaya; Chiara Rizka Yukianti (International Journal of Application on Economics and Business, 2023)
The feasibility study analysis for the Pianeta Gelato business was carried out to present an experience of enjoying ice cream in a different way and concept than usual, as well as to meet market demand which is the foremost opportunity for the establishment of this business. Indonesia's climate and urban lifestyle are the main factors that increase the demand for ice cream products yearly. This Pianeta Gelato business uses a B2C (Business to Consumer) business model. This analysis also aims to find out about business competitors to improve concepts and create appropriate strategies to market this ice cream product to a predetermined target market. The strategy used is to make product concepts and designs that are different from usual, to do the taste by publishing a menu that is the same as the store concept, and to intensify promotions through digital marketing such as social media and KOL to increase public brand awareness. We also use technology that helps in the production and service processes to produce customer satisfaction with our products. The economic benefits obtained from this business are helping the Indonesian economy, providing job opportunities, helping local MSMEs using raw materials, and increasing state income through taxes paid. This ice cream business also pays attention to and supports sustainable development goals through environmentally friendly packaging and waste treatment carried out according to procedures.